All-Organic Semiconductors for Electrochemical Biosensors: An Overview of Recent Progress in Material Design - Hopkins, Jonathan; Fidanovski, Kristina; Lauto, Antonio; Mawad, Damia (Frontiers in Bioengineering and Biotechnology, 2019)
Organic semiconductors remain of major interest in the field of bioelectrochemistry for their versatility in chemical and electrochemical behaviour. These materials have been tailored using organic synthesis for use in cell stimulation, sustainable energy production, and in biosensors. Recent progress in the field of fully organic semiconductor biosensors is outlined in this review, with a particular emphasis on the synthetic tailoring of these semiconductors for their intended application. Biosensors ultimately function on the basis of a physical, optical or electrochemical change which occurs in the active material when it encounters the target analyte. Optical and electrochemical biosensors are most common among organic semiconductor biosensors, and the latter are considered more sensitive and simpler to analyse quantitatively. Electrochemical biosensors can be considered either ‘direct’; where the analyte interacts directly with the semiconductor material in a redox process, or ‘indirect’; where the analyte undergoes a redox process with a moiety such as an enzyme and the electrochemical signal is transduced through to the semiconductor material. The most recent examples of direct and indirect organic semiconductor biosensors are discussed here, mostly comprising of conjugated polymers and polymer semiconducting dyes. We conclude that direct electrochemical biosensors tend to be more sensitive and cost effective, despite indirect biosensors being more common, and encourage the development of direct sensing functionalities. It is also worth noting the role that small molecule semiconductors, such as the photochromic and redox active molecule spiropyran, could play in future as polymer pendant groups for novel organic semiconductor materials.